The Profile of Collaboration Skills of Science Students in SMA Negeri 07 Surakarta - Anita Rahmawati Sutanto; Astried Pascafitri Harenda; Myanda Azkya Arsyi; Suci Nur Cahyani; Baskoro Adi Prayitno (Jurnal Pendidikan Biologi, 2021)
Collaboration skills between students are needed to optimize learning outcomes. Collaboration skills in learning can allow students to exchange information and ideas with their friends, therefore can increasing students' understanding of a material. This study aims to determine the collaboration skills and find out the differences of collaboration skills on science students grade X, XI, and XII in SMA N 07 Surakarta. This study used survey method. Population of this study included all students of grade X, XI, XII, in total 600 students. Stratified proportional random sampling was used as sampling technique with a sample of 20 students at each grade. Student collaboration skills are measured using questionnaires. Data analysis used quantitative description analysis and ANOVA. The results of the study showed that the profile of the X, XI and XII science students' collaboration skills in SMA N 07 Surakarta was in the range of 70-74% or in the high category. There is no difference in the collaboration skills of science students of grade X, XI, and XII (α = 0.412> 0.05).